2008
DOI: 10.1002/app.28532
|View full text |Cite
|
Sign up to set email alerts
|

Free radical polymerizations of some vinyl monomers in carbon dioxide fluid

Abstract: The effect of pressure ranging from ambient atmosphere to 28.5 MPa on the free radical polymerizations of methyl methacrylate (MMA) in carbon dioxide (CO 2 ) was investigated and discussed. The poly (methyl methacrylate) (PMMA) with high molecular weight was synthesized at quite high conversion of MMA in the polymerization at or below 9.2 MPa, as compared to those polymerized under 11.8-28.5 MPa. A phase transition behavior of MMA-CO 2 binary mixture from homogeneous state to vapor-liquid equilibrium (VLE) sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
1
6
0
1
Order By: Relevance
“…Copolymerization was started in a homogenous scCO 2 medium, but when the conversion increased sufficiently in a short period of time, the copolymerization medium was changed into a heterogeneous system consisting of scCO 2 and liquid CO 2 , especially for the copolymerizations containing high MMA content. Thus, the increase in the Zonly-TM content in the feed resulted in the increase in the duration of the homogeneous polymerization in scCO 2 causing the decrease of the copolymer M w consistent with the literature [44].…”
Section: Copolymer Characterizationsupporting
confidence: 84%
See 2 more Smart Citations
“…Copolymerization was started in a homogenous scCO 2 medium, but when the conversion increased sufficiently in a short period of time, the copolymerization medium was changed into a heterogeneous system consisting of scCO 2 and liquid CO 2 , especially for the copolymerizations containing high MMA content. Thus, the increase in the Zonly-TM content in the feed resulted in the increase in the duration of the homogeneous polymerization in scCO 2 causing the decrease of the copolymer M w consistent with the literature [44].…”
Section: Copolymer Characterizationsupporting
confidence: 84%
“…Above this MMA content ratio, the copolymerization medium changed from homogenous to heterogeneous [43]. Wang et al indicated that vinyl monomer polymerization like MMA conversion and M w of the PMMA were increased at the pressure decreasing MMA-CO 2 mixture at vapor-liquid equilibrium pressure including CO 2 and MMA liquids and vapors [44]. They suggested that this phenomena was related to the presence of MMA monomer in the liquid CO 2 phase with higher concentration than that of the homogenous phase, so the polymerization rate in liquid CO 2 phase was faster than the homogenous phase [44].…”
Section: Copolymer Characterizationmentioning
confidence: 96%
See 1 more Smart Citation
“…However, it was found that the binary interaction parameters of C 2 H 2 , CO 2 , CH 3 CHO, and VAc in the thermodynamic models, such as UNIQUAC, NRTL, and Wilson, were missing in the modern modeling packages (such as PROII, Aspen, and ChemCAD). Although fitting binary VLE experimental data is the most accurate and feasible method to obtain binary interaction parameters, there are few experimental data about gas and VAC mixtures and also only a limited number of data about the CH 3 CHO-VAc system and C 2 H 2 -CO 2 were reported. Meanwhile, because the VLE data of the VAC-C 2 H 2 system was difficult to measure, only the data from −15 to 20 °C were measured by Kizlink et al…”
Section: Introductionmentioning
confidence: 99%
“…Η συµπεριφορά αυτά µπορεί να εξηγηθεί βάσει του γεγονότος ότι όσο αυξάνεται ο αριθµός των ατόµων φθορίου στην πολυµερική αλυσίδα, τόσο αυξάνεται και η δυσδιαλυτότητά τους Στο διάγραµµα που ακολουθεί φαίνεται η µεταβολή της πίεσης σε σχέση µε το χρόνο πολυµερισµού και προκύπτει ότι και στις δυο περιπτώσεις η τελική πίεση είναι µεγαλύτερη από την αρχική. Παρόµοια συµπεριφορά παρατηρείται σε αντίστοιχες µελέτες που αφορούν τον πολυµερισµό βινυλικών µονοµερών [Chatzidoukas, et al, 2003, Hsiao, et al, 1995, Kwon, et al, 2004, Lepilleur, et al, 1997, Wang, et al, 2008. Πιο συγκεκριµένα, προκύπτει ότι για αρχικές πιέσεις κάτω από περίπου 230 bar η τελική πίεση είναι µεγαλύτερη από την αρχική [Chatzidoukas, et al, 2003].…”
Section: σύνθεση φθοριωµένων µεθακρυλικών πολυµερώνunclassified